2019
DOI: 10.1155/2019/1371758
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone, a Ligand to PPARγ, Improves Blood Pressure and Vascular Function through Renin-Angiotensin System Regulation

Abstract: Rosiglitazone (RGZ), a peroxisome proliferator-activated receptor gamma (PPARγ) ligand, has been reported to act as insulin sensitizer and exert cardiovascular actions. In this work, we hypothesized that RGZ exerts a PPARγ–dependent regulation of blood pressure through modulation of angiotensin-converting enzyme (ACE)-type 2 (ACE2)/angiotensin-(1-7)/angiotensin II type-2 receptor (AT2R) axis in an experimental model of high blood pressure. We carried on experiments in normotensive (Sham) and aortic coarctation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 44 publications
0
25
0
1
Order By: Relevance
“…17 Preclinical data support the hypothesis that long-term intake of ACE inhibitors, ARBs, statins, corticosteroids, and hypoglycemic agents may increase susceptibility to SARS-CoV-2 infection by favoring viral replication owing to upregulation of ACE2 receptors. [27][28][29][30][31] On the other hand, in patients with COVID-19, these same drugs may theoretically improve the clinical course by rebalancing the dysregulated renin-angiotensin system and thus reducing vasoconstriction, inflammation, and oxidation. In a recent large case series, mortality of patients with hypertension taking ACE inhibitors or ARBs was higher than that of patients with hypertension not taking these drugs, but no statistic confirmed the association between chronic therapy with ACE inhibitors or ARBs and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…17 Preclinical data support the hypothesis that long-term intake of ACE inhibitors, ARBs, statins, corticosteroids, and hypoglycemic agents may increase susceptibility to SARS-CoV-2 infection by favoring viral replication owing to upregulation of ACE2 receptors. [27][28][29][30][31] On the other hand, in patients with COVID-19, these same drugs may theoretically improve the clinical course by rebalancing the dysregulated renin-angiotensin system and thus reducing vasoconstriction, inflammation, and oxidation. In a recent large case series, mortality of patients with hypertension taking ACE inhibitors or ARBs was higher than that of patients with hypertension not taking these drugs, but no statistic confirmed the association between chronic therapy with ACE inhibitors or ARBs and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the peroxisome proliferatoractivated receptor-␥ (PPAR-␥) may influence ACE-2 expression as well. The PPAR-␥ agonist rosiglitazone increased ACE2 protein levels twofold in the aorta of hypertensive rats following aortic coarctation (39). Oudit and colleagues (61) found that telmisartan, a partial PPAR-␥ agonist, also increased ACE2 protein expression in aorta which was associated with greater PPAR-␥ content in the spontaneously hypertensive rat.…”
mentioning
confidence: 97%
“…Thus, the ACE2 peptidase pathway constitutes a key inflexion point in the processing pathway of the RAAS. Consequently, the loss of ACE2 may shift the system to an overall higher ANG II and lower Ang-(1-7) tone (4,5,39). In contrast, ACE forms ANG II and degrades Ang-(1-7), which produces the opposite processing of ACE2 and promotes an increase in blood pressure, inflammation, and fibrosis ( Fig.…”
mentioning
confidence: 99%
“…Of note, Ang II circulatory levels correlated well with viral load and negative cardio-respiratory function in the SARS-CoV-2 patient cohort [41]. The role of PARP in the modulation of ACE2 was also implicated in hypertensive rats, where inhibition of PARP could enrich ACE2 protein levels [153]. These data could explain the high prevalence (15-40%) of hypertension in COVID-19 patients [2,154] that increases further with disease severity [154].…”
Section: Ace2 and Potential Cardiovascular Risk Factorsmentioning
confidence: 86%